Exploiting databases and computer softwares in drug formulation: Mining the treasures - Rania M Hathout; AbdelKader A Metwally (Open Journal of Chemistry - Peertechz Publications, 2018)
In one of the conversations between me and one of my senior colleagues, she told me "What lucky researchers you are!", interested to know the reason behind this statement, I asked: "Why?!", and she replied: "because in our time we didn't have all these available search engines, scientific databases, open resources and data manipulation tools". Later, I had a discussion with one of my colleagues - now we are co-authors - who expressed his interest in examining new aspects of formulation: "we can use computer simulations to examine many aspects of different formulations, literally virtualizing our lab" he said.